Copper-Catalyzed One-Pot Synthesis of Functionalized 1,4-Dihydroazete Derivatives from Sulfonyl Azides, Terminal Alkynes, and Tetramethylguanidine - Yavari, Issa; Nematpour, Manijeh (Synlett, 2012)
Ketenimine intermediates generated by the addition of copper acetylides to sulfonyl azides are trapped by tetramethylguanidine to afford 1,4-dihydro-N,N-dimethyl-3-aryl(alkyl)-4-aryl(alkyl)sulfoniminoazet-2-amine derivatives in moderate to good yields.
Keywords: 1,4-dihydroazete; copper iodide; tetramethylguanidine; sulfonyl azide; terminal alkyne; ketenimine